2020
DOI: 10.1155/2020/8125758
|View full text |Cite
|
Sign up to set email alerts
|

Sikyungbanha‐Tang Suppressing Acute Lung Injury in Mice Is Related to the Activation of Nrf2 and TNFAIP3

Abstract: Sikyungbanha-Tang (SKBHT) is a Chinese traditional medicine popularly prescribed to patients with respiratory inflammatory symptoms in Korea. Although the Korea Food and Drug Administration approved SKBHT as a therapeutics for relieving the symptoms, experimental evidence for SKBHT suppressing inflammation is scarce. Here, we presented evidence that SKBHT can suppress inflammation in an acute lung injury (ALI) mouse model and explored the possible underlying mechanisms of SKBHT's anti-inflammatory activity. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…5A, B). We found that chemokines (GPR-35, CXCL15, CCL5, and CCR2) involved in the macrophages and neutrophils recruitment [19,[23][24][25] were significantly elevated, while the negative regulator of macrophages activation KLF2 was downregulated in IL-10 B-KO lungs (Fig. 5C).…”
Section: Il-10 In B Cells Promotes Ali Recovery Possibly Via the Cgmp...mentioning
confidence: 86%
“…5A, B). We found that chemokines (GPR-35, CXCL15, CCL5, and CCR2) involved in the macrophages and neutrophils recruitment [19,[23][24][25] were significantly elevated, while the negative regulator of macrophages activation KLF2 was downregulated in IL-10 B-KO lungs (Fig. 5C).…”
Section: Il-10 In B Cells Promotes Ali Recovery Possibly Via the Cgmp...mentioning
confidence: 86%
“…Tumor necrosis factor alpha-induced protein 3 (TNFAIP3) is an important deubiquitinating enzyme that has an impact on tumorigenesis, immune responses, and inflammation [ 30 , 31 ]. The function of TNFAIP3 mainly relies on its ubiquitin degradation to regulate intracellular protein expression [ 32 ]. Recent studies suggested that TNFAIP3 may have a vital role in the invasion and proliferation of lung cancer and gastric cancer [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor alpha-induced protein 3 (TNFAIP3) is an important deubiquitinating enzyme that has an impact on the tumorigenesis, immune responses and in ammation (Du et al 2019;Liao et al 2020). The function of TNFAIP3 mainly relies on its ubiquitin degradation for intracellular protein expression (Kim et al 2020). Recent studies suggested that TNFAIP3 may have vital role in the invasion and proliferation of lung cancer and gastric cancer (Liao et al 2020;Wisnieski et al 2020).…”
Section: Discussionmentioning
confidence: 99%